PREDIKSI POLA SEBARAN PLUME RISE PADA VARIASI KECEPATAN EMISI GAS BUANG CHIMNEY DENGAN SIMULASI KOMPUTER - Muhammad Nur Shobakh; Agung Sugeng Widodo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
One of the most significant current issues that endangers environment is air pollution from industrial chimney emissions. In certain condition, the mathematical models to analyze this problem is the Gaussian Plume Model (GPM), which is a model of air pollutant distribution that takes place under constant conditions and is based on the Gaussian distribution. This model was developed based on the diffusion equation to determine the pollutant concentration from a single point source located at a certain altitude and terrain. The aim of this research was to investigate Simulating the dispersion pattern of pollutant gas plume rise from the chimney to the environment using Ansys Workbench software, analyze the shape of the plume rise dispersion pattern and investigate factors influence the plume rise in the chimney. The results showed that the plume rise dispersion pattern that occurred in this study is lofting. The higher the velocity of exhaust emissions coming out of the chimney, the higher the plume rise that occurs into the atmosphere. The factors that can affect the plume rise dispersion pattern in the chimney are the wind speed factors, the atmospheric air temperature factors, and the air stability factors.